Estimulación de la masa radicular para mejorar la sanidad en el cultivo de banano (Musa AAA) - MORA MOSQUERA, MELWIN MAXIMILIANO (2023)
In the banana, special attention must be paid to its root system, to ensure that it is taking advantage of the necessary elements for efficient operation. The use of biostimulants are substances that favor the growth and development of plants, making them more resistant to adverse conditions such as droughts or pest attacks, as well as improving their metabolism. With the general objective of describing the advantages and disadvantages of biostimulants to improve the root mass of the banana crop (Musa AAA). This document was developed with the purpose of compiling all kinds of information, carrying out a detailed investigation in the various web pages, scientific articles, sources and bibliographic documentation available on digital platforms. Having as a result that the Rooting biostimulant gives a greater root length and a better appearance to the plant, also that when applying humic acids with chemical fertilization it favors the development of the plants such as plant height, pseudostem diameter, foliar emission, flowering and fruiting and chemical and organic rooting treatments (3 liters of Equilibri + 5 kg of Biochar), it has an absence of 7 pathogens and increases the amount of presence of 4 beneficial microorganisms, highlighting the genus Trichoderma spp., a biological controller of nematodes, Fusarium and Rhizoctonia. Concluding that at the moment of stimulating the root mass of the banana, since it improves the absorption of nutrients, making the plant supply the necessary elements for its growth and can carry out all its physiological processes, generating a plant with a good quality of fruit and good production.